Gas sensing properties of nanocrystalline diamond at room temperature - Davydova, Marina; Kulha, Pavel; Laposa, Alexandr; Hruska, Karel; Demo, Pavel; Kromka, Alexander (Beilstein Journal of Nanotechnology, 2014)
This study describes an integrated NH3 sensor based on a hydrogenated nanocrystalline diamond (NCD)-sensitive layer coated on an interdigitated electrode structure. The gas sensing properties of the sensor structure were examined using a reducing gas (NH3) at room temperature and were found to be dependent on the electrode arrangement. A pronounced response of the sensor, which was comprised of dense electrode arrays (of 50 µm separation distance), was observed. The sensor functionality was explained by the surface transfer doping effect. Moreover, the three-dimensional model of the current density distribution of the hydrogenated NCD describes the transient flow of electrons between interdigitated electrodes and the hydrogenated NCD surface, that is, the formation of a closed current loop.
Keywords: gas sensor; integrator; interdigitated electrodes; nanocrystalline diamond; response